136 Gp auscultation for diagnosing valvular heart disease. (5th June 2017) - Myerson, Saul; Prendergast, Bernard; Gardezi, Syed; Prothero, Anthony; Kennedy, Andrew; Wilson, Joanna
Abstract : Introduction: Cardiac auscultation is an important clinical skill used by physicians in assessing and diagnosing valvular heart disease (VHD). The widespread use of echocardiography in the last three decades has coincided with a perceived decline in the utility of auscultation, particularly by general physicians. The ability of generalists to identify VHD in an unselected population has not been well characterised, so we aimed to determine the accuracy of auscultation in primary care for diagnosing VHD. Methods: 251 participants aged 65 and over who were participating in the OxValve population cohort study were included. They were recruited from two participating GP surgeries and had no previous diagnosis of VHD. The participants underwent cardiac auscultation during the OxValve study visit by two experienced General Practitioners (GPs), neither of whom had a specialist interest in cardiology. A 5-point Likert scale was used to rate the ability to hear heart sounds (1=not at all; 5=perfectly) in addition to the presence or absence of a murmur, type of murmur and the ability to make a diagnosis based upon the auscultation findings. This was compared to transthoracic echocardiography performed at the same visit, but GPs were blind to the echocardiogram result, which was performed after auscultation. VHD was categorised as mild (either mild regurgitation [excluding trace/physiological] or aortic sclerosis) or significant (moderate/severe regurgitation or at least mild stenosis). Standard measures of diagnostic accuracy were calculated. Results: 82 murmurs were heard by the GPs (80 systolic; 2 diastolic). Echocardiography identified mild VHD in 174 (69%) of the 251 participants, with more significant VHD present in 37 (15%). The ability to hear a murmur on auscultation was not related to age, BMI or heart rate (table 1). Auscultation had a sensitivity of 32% and specificity of 67% for diagnosing mild VHD, which improved slightly for significant VHD to a sensitivity of 43%, and specificity of 69% (table 2). The area under the curve on receiver operating characteristics (ROC) analysis was 0.50 for mild VHD and 0.56 for significant VHD (Figure-1) suggesting limited discriminatory ability. Conclusion: GP auscultation has only moderate accuracy for diagnosing valvular heart disease in an unselected population, and the presence of an isolated murmur would not be a reliable indicator of valve disease. This study did not include patients with cardiovascular symptoms however, in whom the presence of a murmur may be more significant, and for whom echocardiography might be more appropriate.